Historikalitas Puisi Menuai Buah Kehidupan Karya Orang Muda Katholik Lingkungan Velentinus Paroki Aloysius Gonzaga Cijantung: Tinjauan Hermeneutik Wilhelm Dilthey - Endang Sulistijani (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
Millineal learn to be care to their environment through poem. Poem helps them to understand the way people thought or felt. These focuses using Wilhelm Dilthey hermeneutic include Erlebnis and Ausdruck. The theme was Wise to Your Nature for the Sustainability, from Jakarta Diosesan Church. It helps people to be care with the nature. Its strart from reducing plactic, caring to other people, cleaned up our neighbourhood, and others. These theme was the continued from last year theme, and focused on environtment. Now a days we face our earth more and more damaged because our life style. The Jakarta’s Bishop concerned about this, and asking us to fight for save our planet. Using this theme, means that all of us being invited to act in our daily days. We use young people because they were a person who’s continued this world. Asked them to care mean invited them to live wise for their sustainable life. Simple act such as not to be acquisitived, cared, sage, and kindful, help them to realized that live is tought us that everything must be prevented to be sustainable. If our environment cleans, our pla